The Role of Head of Public Secondary Schools in Providing Professional Development to Enhance Teacher Job Satisfaction in Arumeru District, Tanzania (International Journal of Scientific Research and Management (IJSRM), 2025)
The study examined the role of the head of public secondary schools in providing professional development to enhance teacher job satisfaction in Arumeru district, Tanzania. The study was guided by the Path-Goal Leadership Theory. The study employed a convergent design under the mixed-methods research approach. The target population comprised 30 public secondary schools, 30 heads of schools, 1227 teachers, and 1 District Secondary Education Officer (DSEO). The study employed probability and non-probability sampling procedures to select 8 public secondary schools, 8 heads of schools, 128 teachers, and 1 District Secondary Education Officer (DSEO). Questionnaires and interview guides were validated by research experts in the field of education from Mwenge Catholic University, MWECAU. A pilot study was conducted in two public secondary schools, and the reliability of questionnaires for Likert-type items was established at 0.823 Cronbach’s Alpha Coefficient. The dependability of the qualitative data was established through peer debriefing and triangulation methods. Quantitative data were descriptively deduced into frequencies, percentages, and means, aided by Statistical Package for the Social Sciences SPSS version 22 and presented in tables. Qualitative data were analyzed thematically. The study adhered to research ethical principles throughout the research process. The findings showed that providing professional development opportunities enhances job satisfaction. The study concluded that sustaining extrinsic motivational strategies such as professional development opportunities significantly enhances teacher job satisfaction in public secondary schools in Arumeru District, Tanzania. It is recommended that school heads prioritize and maintain this strategy to improve teacher morale, collaboration, and overall effectiveness.